TINGKAT PEMAHAMAN GURU TERHADAP PENERAPAN PEER-LEARNING SEBAGAI MODEL PEMBELAJARAN INOVATIF DI SEKOLAH - Komara, Endang; Karlina, Haura; Nisa, Zakia Hary; Suryadi, Toto (Universitas Tanjungpura, 2024)
This study emphasizes the significance of providing teachers with opportunities to develop their capacity to implement innovative peer-learning strategies. The research also emphasizes the necessity for educational institutions to guarantee equitable access to resources and facilities to facilitate the implementation of optimal peer-learning strategies. This study employs a framework for analyzing industrial transformation and educational innovation. Students, academics, instructors, heads of educational institutions, and government officials were among the approximately 20 respondents in the study. The focus of the study was on two case studies examining the contribution of peer learning in Physics classes at two Jakarta secondary institutions. Since Physics is one of the principal subjects for which interactive learning methods have been extensively developed, research findings indicate that respondents agree that peer learning is an innovative and engaging method. However, participant teachers' comprehension of the potential of peer learning varied. Some instructors have a solid grasp of the concept and its benefits, whereas others have a limited grasp.